PERANCANGAN PROGRAM APLIKASI PENJUALAN BERBASIS WEBSITE PADA PT.INDOMETIC - Florensia Louhenapessy (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
Sales Application Program Design Based Website at. Indometic was made to improve the effectiveness of the company's performance and deliver. In addition, as a means of information about PT.Indometic .The methodology used in this design is a prototype methodology. For a depiction of the draft then used flowcharts, Context Diagram, DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), and the relationships between tables . The programming language used is PHP, some other software in use is the Operating System Windows 7 Starter 32 Bit, Mozilla Firefox Web Browser Applications, XAMPP to run the database through phpMyAdmin .